(untitled) - Bulme, Martin; edited by Martin Bulmer and John Solomos (Oxford,New York, 1999)
W. E. B. DuBois wrote in 1903 that "the problem of the twentieth century is the problem of the color line--the relation of the darker to the lighter races in the various areas of the world in which they interact." As the century draws to its close, this remains true; the last few years have witnessed a growth in academic interest in racism and an increasing general awareness of various kinds of racial conflict and violence in areas around the globe. This Oxford Reader provides a critical overview of the historical development and contemporary forms of racist ideas and institutions. It brings together material from different theoretical perspectives in an attempt to make sense of the ways in which racism has exerted such a powerful influence on the history of humanity
Keywords: Racism